Resilience as a Predictor of Psychological Recovery among Trauma Survivors: A Cross-Sectional Quantitative Study - Maqhfirah DR (Manunggal Halim Jaya, 2026)
Traumatic experiences often result in psychological distress that impairs individuals' emotional, social, and daily functioning. Nevertheless, not all trauma survivors experience prolonged psychological difficulties, as many demonstrate the capacity to achieve psychological recovery. Resilience has been widely recognized as an important protective factor that facilitates positive adaptation following traumatic experiences. Therefore, this study aimed to examine the role of resilience in predicting psychological recovery among trauma survivors. A quantitative, cross-sectional, correlational design was employed, involving 128 trauma survivors selected using purposive sampling. Resilience was assessed using the Connor–Davidson Resilience Scale-10 (CD-RISC-10), whereas psychological recovery was measured using the Questionnaire about the Process of Recovery (QPR-15). Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The findings revealed that resilience was positively and significantly associated with psychological recovery (r = .624, p < .001) and emerged as a significant predictor (β = .624, p < .001), explaining 38.9% of the variance in psychological recovery (R² = .389). These findings indicate that individuals with higher resilience are more likely to achieve better psychological recovery following traumatic experiences. The study provides empirical evidence supporting resilience as a key psychological resource in post-traumatic adaptation and highlights the importance of resilience-based interventions to facilitate psychological recovery among trauma survivors.